Karakteristik Kayu Sanrego (Lunasia Amara Blanco) Sebagai Salah Satu Potensi Indikasi Geografis Di Kabupaten Bone - Jainuddin, Asyraf; Paserangi, Hasbir; Marwah, Marwah (Universitas Ekasakti, 2023)
This study aims to identify and describe the characteristics of sanrego wood so that it can be protected by the intellectual property rights act in the form of legal protection for geographical indications and to examine local government efforts for legal protection for geographical indications for sanrego Bone wood. This research uses the type of empirical research. Legal research is carried out by examining existing facts in line with observations in the field so that they can reveal in detail and explore the object being observed. This research was conducted in Bone Regency, South Sulawesi Province an the Ministry of Law and Human Rights of South Sulawesi.The data obtained was colleted through this study by data processing, both primary data and secondary data, all data were analyzed qualitatively. The results of the study show that: (1) Sanrego wood has the potential to obtain legal protection for Geographical Indications because of its reputation, quality and characteristics. Based on Laboratory Tests, Sanrego wood contains active compounds, namely, flavonoids, alkaloids, and steroids ehich function as aphrodisiacs. Sanrego wood has also met standardization as a traditional medicine according to the Decree of the Director General of Drug and Food Control Number: 03726/B/SK/VII/89. (2) The Government of Bone Regency is expected to make efforts to legally register the geographical indications of sanrego timber as a step to obtain legal protection and legal certainty as well as to obtain exclusive rights and economic benefits, as stipulated in Law Number 20 of 2016 concerning Trademarks and Geographical Indications.